Памятники покровского типа на современном этапе изучения в российской и украинской археологии - Пряхин, А.Д. (My University, 2011)
Пряхін А. Д. Пам’ятки покровського типу на сучасному етапі дослідження в російській та українській археології В археології існує декілька підходів до оцінки пам’ятників покровського типу заключного етапу середньої—початку пізньої бронзи степової та лісостепової зон доно-донецького регіону та волго-уральських просторів: покровська археологічна культура, покровська зрубна культура, покровська абашевська культура, покровський культурний тип. Обґрунтовується необхідність оцінки пам’ятників покровського типу в системі абашевського та зрубного світів як проміжної ланки між ними. A. Priakhin. sites of “Pokrovskiy” Type as Defined by the current stage Archeological studies in Russia and Ukraine Modern archaeology takes different approaches to the interpretation of the Pokrovsky type sites located in the steppe and forest-steppe Don-Donetsk and Volga-Ural regions at the end of the middle — beginning of the late Bronze Age. These sites are defined as the Pokrovsky archaeological culture, the Pokrovsky Srubnaya (Timber-grave) culture, the Pokrovsky Avashevo culture and the Pokrovsky cultural type. The article validates the interpretation of the Pokrovsky type sites in the system of Abashevo and Srubnaya antiquities as a transitional link between them.
Keywords: покровська археологічна культура; покровська зрубна культура; покровська абашевська культура; покровський культурний тип; Pokrovsky archaeological culture; Pokrovsky Avashevo culture; Pokrovsky cultural type